Promoting intentions to persist in computing: an examination of six years of the EarSketch program. Issue 4 (1st October 2020) - Wanzer, Dana Linnell; McKlin, Tom; Freeman, Jason; Magerko, Brian; Lee, Taneisha
ABSTRACT: Background and Context : EarSketch was developed as a program to foster persistence in computer science with diverse student populations. Objective : To test the effectiveness of EarSketch in promoting intentions to persist, particularly among female students and under-represented minority students. Method : Meta-analyses, structural equation modeling, multi-level modeling, and qualitative analyses were performed to examine how participation in EarSketch and other factors affect students' intentions to persist in computing. Findings : Students significantly increased their intentions to persist in computing, g = .40[.25, 54], but examination within just the five quasi-experimental studies did not result in a significant difference for students in EarSketch compared to students not in EarSketch, g = .08[−.07, .23]. Student attitudes towards computing and the perceived authenticity of the EarSketch environment significantly predicted intentions to persist in computing. Implications : Participation in computer science education can increase students' intentions to persist in programming, and EarSketch is one such program that can aid in these intentions.